The “Affreux”: French mercenaries, types of violence and systems of domination by extra-African forces (1960-1989) - (:unkn) unknown (My University, 2014)
The revival of mercenaries is a phenomenon occurring concomitantly with the African decolonization. From 1960 to the end of the Cold War, mercenaries took part in the development of political and armed violence on the African continent. They are interesting, first of all, because, thanks to these paramilitary actors, we are able to understand the linkages between the numerous actors who contribute to the implementation of an underlying violence of the political life in post-colonial Africa from the 60’s to the end of the Cold War. The book aims at highlighting their actions and questioning the modalities of implementing violence in which the mercenaries are just instruments during this period. Who are their sleeping partners? By which means can the “Affreux” act? Those questions imply analysing their links and interactions with global private forces (mining industry, arms traffic), with non-African actors trying to impose their influence, and also with the African powers themselves.
Keywords: African Research